INKONSISTENSI PERATURAN BUPATI KABUPATEN TANAH DATAR NOMOR 48 TAHUN 2020 TENTANG PENERAPAN DISIPLIN PROTOKOL COVID-19 DENGAN ASAS PEMBUATAN PERUNDANG-UNDANGAN DAN HUKUM TATA NEGARA ISLAM - Nori Tiara Andika; Saadatul Maghfira; Zainuddin Zainuddin; Nurhikma Nurhikma (JISRAH: Jurnal Integrasi Ilmu Syariah, 2023)
This study examines the inconsistency of Tanah Datar District Head Regulation Number 48 of 2020 concerning the application of the Covid-19 protocol discipline with the principles of making legislation, both formal principles, namely: the principle of applicability and material principles, namely: the principle of openness, the principle of legal certainty. The two causative factors that influence the existence of inconsistency include the following internal factors: age factor, habit factor while external factors are as follows: educational factor, economic factor and work. The application of the Tanah Datar District Head's regulation Number 48 of 2020 concerning the application of the disciplinary protocol for the Covid-19 is not in accordance with the constitutional law of the Islamic state. Because in Islamic constitutional law it has been explained how the concept of implementing Islamic shari'ah is for us to obey the rules that have been made by the rulers or the government. However, in reality the community does not comply with the Tanah Datar District Regent Regulation Number 48 of 2020 concerning the application of the co-19 protocol discipline.